Notch signaling in the pigmented epithelium of the anterior eye segment promotes ciliary body development at the expense of iris formation. (7th April 2014) - Sarode, Bhushan; Nowell, Craig S.; Ihm, JongEun; Kostic, Corinne; Arsenijevic, Yvan; Moulin, Alexandre P.; Schorderet, Daniel F.; Beermann, Friedrich; Radtke, Freddy
Summary The ciliary body and iris are pigmented epithelial structures in the anterior eye segment that function to maintain correct intra‐ocular pressure and regulate exposure of the internal eye structures to light, respectively. The cellular and molecular factors that mediate the development of the ciliary body and iris from the ocular pigmented epithelium remain to be fully elucidated. Here, we have investigated the role of Notch signaling during the development of the anterior pigmented epithelium by using genetic loss‐ and gain‐of‐function approaches. Loss of canonical Notch signaling results in normal iris development but absence of the ciliary body. This causes progressive hypotony and over time leads to phthisis bulbi, a condition characterized by shrinkage of the eye and loss of structure/function. Conversely, Notch gain‐of‐function results in aniridia and profound ciliary body hyperplasia, which causes ocular hypertension and glaucoma‐like disease. Collectively, these data indicate that Notch signaling promotes ciliary body development at the expense of iris formation and reveals novel animal models of human ocular pathologies.